Nanoplasmonic ruler to measure lipid vesicle deformation - Jackman, Joshua A. (2016)
A nanoplasmonic ruler method is presented in order to measure the deformation of adsorbed, nm-scale lipid vesicles on solid supports. It is demonstrated that single adsorbed vesicles undergo greater deformation on silicon oxide over titanium oxide, offering direct experimental evidence to support membrane tension-based theoretical models of supported lipid bilayer formation.